The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1809-4430-eng.agric.v37n1p91-97/2017
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an Agricultural Diesel Engine Using Differents Fuels

Abstract: ABSTRACT:The use of fuels for agricultural Diesel engines cycle, both of mineral origin (Diesel) or vegetable and animal origin (biodiesel) can significantly alter its performance. Therefore, the aim of this study was to quantify the change in torque, power and consumption of agricultural Diesel engine fuel using minerals and vegetables fuels. It was used a tractor power take-off coupled to a magnetic brake dynamometer (for measuring speed and torque for subsequent calculation of power), and a flow meter (for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(15 reference statements)
1
0
0
1
Order By: Relevance
“…The lower calorific value and the change in the behavior of the heat release during the combustion process are factors that highlight the need for engine adjustments to obtain a better performance and lower specific consumption with these fuels. The results follow the same trend as that reported by Perin et al (2017), who found that the specific consumption increased by 7.10% and 9.33% for B20 and B50, respectively, compared to B10. Godeša et al (2010), on the other hand, observed corresponding increases in the specific consumption of 1.25% and 2.5% for B20 and B30, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The lower calorific value and the change in the behavior of the heat release during the combustion process are factors that highlight the need for engine adjustments to obtain a better performance and lower specific consumption with these fuels. The results follow the same trend as that reported by Perin et al (2017), who found that the specific consumption increased by 7.10% and 9.33% for B20 and B50, respectively, compared to B10. Godeša et al (2010), on the other hand, observed corresponding increases in the specific consumption of 1.25% and 2.5% for B20 and B30, respectively.…”
Section: Resultssupporting
confidence: 90%
“…As máquinas agrícolas são empregadas para realizar diversas operações ao longo do processo produtivo, sendo o combustível um fator que representa elevado custo aos produtores (PERIN et al, 2017). Diante desta conjuntura, a indústria de máquinas agrícolas busca o desenvolvimento e a implementação de novas tecnologias em seus motores que visam, principalmente, o aumento da eficiência e otimização de recursos, culminando com a redução dos níveis de emissões.…”
Section: Introductionunclassified